Per una ennesima tipologia di lettore - Magrelli, Valerio (Dialogoi. Rivista di studi comparatistici, 2020)
For decades, the figure of the great excluded third, the reader, has been introduced into the privileged relationship between author and work. If in a structuralistic climate the analysis of the text was privileged, the discussion was later modeled on the pragmatics of reading: the Anthropology of writing examined by the dear Giorgio Raimondo Cardona has now been accompanied by a real “anthropology of reading”. This play of roles has given rise to an extremely complex series. Well, the article intends to present three sub-cases of a further category: that of “sick reader”, or “injured reader”, therefore, implicitly, guilty of “injured reading”.